Optimizing Early Childhood Education in Efforts to Create Superior Quality Human Resources in Indonesia - Rahmi Kurnia; Rizka Mutiah Nur; Isda Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
Education is something that must exist in each individual. Without the provision of education, a nation cannot become a developed and competitive country in the era of globalization. If the quality of education is low then the quality of the tablespoons will also be low. Education has a very important meaning for the growth of children because children are potential leaders of the nation. In this study, researchers used a type of literature review research and used data obtained from literature studies. The data obtained were analyzed using descriptive analysis method. The results of this study indicate that there are several aspects that need attention in efforts to optimize PAUD in Indonesia, namely regarding the quality of facilities and infrastructure in PAUD institutions, equitable distribution of education in cities and villages, parental awareness about the importance of PAUD, quality of educators in PAUD institutions. Increasing the operational budget of education, equitable distribution of education in cities and villages, increasing parental awareness about the importance of PAUD through counseling and outreach, improving the quality of educators in PAUD institutions can be done through education and training for prospective educators is an effort and effort that can be done to optimize PAUD in Indonesia.Keywords: Early Childhood, PAUD, Government, Educators, Parents